2015
DOI: 10.1038/srep11916
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Scaffold is a Double-Stranded Assembly of Scaffold Proteins

Abstract: Chromosome higher order structure has been an enigma for over a century. The most important structural finding has been the presence of a chromosome scaffold composed of non-histone proteins; so-called scaffold proteins. However, the organization and function of the scaffold are still controversial. Here, we use three dimensional-structured illumination microscopy (3D-SIM) and focused ion beam/scanning electron microscopy (FIB/SEM) to reveal the axial distributions of scaffold proteins in metaphase chromosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 27 publications
3
28
0
Order By: Relevance
“…Major scaffold proteins involved in chromosome organization include condensins, topoisomerase IIα (Topo IIα), and kinesin family 4 (KIF4)1113. Although depletion of these proteins disrupts chromosome structure, X-shaped chromosomes are still formed1314. This suggests that scaffold proteins are not the only factors contributing to chromosome condensation.…”
mentioning
confidence: 99%
“…Major scaffold proteins involved in chromosome organization include condensins, topoisomerase IIα (Topo IIα), and kinesin family 4 (KIF4)1113. Although depletion of these proteins disrupts chromosome structure, X-shaped chromosomes are still formed1314. This suggests that scaffold proteins are not the only factors contributing to chromosome condensation.…”
mentioning
confidence: 99%
“…The SMC subunits form pairs at the hinge region to form three different heterodimers that bind three non-SMC subunits; these in turn lead to the establishment of the large, five-subunit condensin, cohesin, and Smc5-6 protein complexes. The Smc1-3 heterodimer is a component of cohesin, which is essential for chromosome cohesion; the Smc2-4 heterodimer is a component of condensin I and condensin II, which are localized to the axis of metaphase chromosomes in a double-stranded manner and contribute to the condensed chromosome structure (3)(4)(5). In addition, as functional studies of condensin, introduction of supercoiling to DNA and reannealing activity that convert single-stranded DNA (ssDNA) into double strand DNA (dsDNA) have been investigated (6 -8), which might be responsible for diverse DNA metabolism mediated by condensin.…”
mentioning
confidence: 99%
“…In vertebrate cells, enrichment of hCAP-E in the centromeric regions of mitotic chromosomes, which contain large amounts of repetitive DNAs, was observed [Poonperm et al, 2015], and condensin II is enriched in the kinetochores during mitosis as its phosphorylation level increases in an aurora B and/or hMis6/CENP-I-dependent manner [Ono et al, 2004;Nakazawa et al, 2008]. Enrichment of condensin in pericentromeric regions was also reported in a number of organisms including budding yeast [Eckert et al, 2007;D'Ambrosio et al, 2008;Kim et al, 2013].…”
Section: Condensin Is Concentrated At the Centromere Or Kinetochorementioning
confidence: 70%
“…Our previous proteome analysis of human metaphase chromosomes indicated that the molar ratio of hCAP-C to 100 molecules of histone H4 is 0.32 at the most, corresponding to condensin binding to the chromatin fiber every 33 kb on average [Uchiyama et al, 2005]. Our recent study using superresolution microscopy revealed that the chromosome scaffold appears at the axis of the sister chromatids, which was first discovered by Paulson and Laemmli [1977] and was later identified as barber pole model [Maeshima and Laemmli, 2003], and is constructed in a twisted doublestranded fashion in each chromatid [Poonperm et al, 2015] ( fig. 2 ).…”
mentioning
confidence: 98%